Bibliometric Reports for Institutions: Best Practices in a Responsible Metrics Scenario - Cabezas-Clavijo, Alvaro; Torres-Salinas, Daniel (Frontiers in Research Metrics and Analytics, 2021)
Carrying out bibliometric reports is one of the common tasks performed by librarians and practitioners within the framework of their professional duties. The emergence of novel data sources, the need to measure new research activities and the growing demand for fairer and more equitable evaluation within the framework of the Responsible Metrics movement has led to calls for a review of the traditional approaches to these types of reports. The main goal of this study is to outline a series of recommendations for bibliometricians, consultants and research support librarians when drafting bibliometric reports in their institutions. These best practices can significantly enhance the quality and utility of bibliometric reports, posing these practitioners as a key factor in the science management process.